INTERVALES: INTERactive Virtual and Augmented framework for industriaL Environment and Scenarios. (October 2021) - Richard, Killian; Havard, Vincent; His, Jordan; Baudry, David
Abstract: One of Industry 4.0's greatest challenges for companies is the digitization of their processes and the integration of new related technologies such as virtual reality (VR) and augmented reality (AR), which can be used for training purposes, design, or assistance during industrial operations. Moreover, recent results and industrial proofs of concept show that these technologies demonstrate critical advantages in the industry. Nevertheless, the authoring and editing process of virtual and augmented content remains time-consuming, especially in complex industrial scenarios. While the use of interactive virtual environments through virtual and augmented reality presents new possibilities for many domains, a wider adoption of VR/AR is possible only if the authoring process is simplified, allowing for more rapid development and configuration without the need for advanced IT skills. To meet this goal, this study presents a new framework: INTERVALES. First, framework architecture is proposed, along with its different modules; this study then shows that the framework can be updated by not only IT workers, but also other job experts. The UML data model is presented to format and simplify the authoring processes for both VR and AR. This model takes into account virtual and augmented environments, the possible interactions, and ease operations orchestration. Finally, this paper presents the implementation of an industrial use case composed of collaborative robotic (cobotic) and manual assembly workstations in VR and AR based on INTERVALES data.